1992
DOI: 10.1007/bf00578297
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of diacetoxyscirpenol and deoxynivalenol on microbicidal activity of murine peritoneal macrophages

Abstract: Diacetoxyscirpenol and deoxynivalenol, two trichothecene mycotoxins shown previously to exert immunosuppressive effects on the immune system were examined for their in vitro effects on some functions of murine peritoneal macrophages. The cells were pre-incubated for 4 hr with the mycotoxin concentrations of 0.1 ng/ml-1 micrograms/ml. At concentrations that did not affect the cell viability (Specific Lactate Dehydrogenase test), diacetoxyscirpenol and deoxynivalenol suppress microbicidal activity of phagocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…A similar decrease in phagocytic activity of antigen-presenting cells in response to DON has been shown for macrophages from mice and turkeys (Ayral et al, 1992;Kidd et al, 1995). Fig.…”
Section: Discussionsupporting
confidence: 54%
“…A similar decrease in phagocytic activity of antigen-presenting cells in response to DON has been shown for macrophages from mice and turkeys (Ayral et al, 1992;Kidd et al, 1995). Fig.…”
Section: Discussionsupporting
confidence: 54%
“…In addition to its direct stimulatory effect, DON at low doses also potentates the stimulatory effects of cytokines/bacterial components on macrophages [124,125]. In parallel to macrophage activation, low doses of DON also affect their ability to phagocytose and to kill bacteria, leading either to a decrease or an increase in the phagocytosis depending of the type of bacteria used in the assay [109,126]. As shown with IEC, higher doses of DON (µM range) possess suppressive effects on macrophage activations (cytokine secretion, phagocytosis, bacterial killing) and induce their apoptosis [124,125,127] such deleterious effects certainly contributing to the observed increase in the susceptibility to infection of animals exposed to DON [119,127,128].…”
Section: Pathophysiological Effects Of Donmentioning
confidence: 99%
“…Ayral et al (48) showed that the trichothecenes diacetoxyscirpenol and deoxynivalenol reduce phagocytosis, suppress microbicidal activity, and inhibit superoxide anion production and phagosome-lysosome fusion of peritoneal macrophages at concentrations that did not affect cell viability. Similarly, Vidal and Mavet (49) demonstrated inhibition of phagocytosis of Pseudomonas aeruginosa by murine peritoneal macrophages in the presence of 0.001 pM T-2 toxin.…”
Section: Effects Of Mycotoxins On Alveolar Macrophages and Immune Funmentioning
confidence: 99%